Increasing Positive Thoughts in Adolescents Through Relaxation Therapy Using Body Sensors: Peningkatan Pikiran Positif Pada Remaja Melalui Terapi Relaksasi Dengan Menggunakan Sensor Tubuh - Yolanda, Lola; Rachmiaty, Sitty; Hidayah, Zeldi (Psikologia : Jurnal Psikologi, 2020)
In adolescents, the influence of technology can have a positive or negative impact. Problems caused by teenagers then need an effort so that they can be handled properly. One of them is to increase positive thoughts. To get positive thoughts can be done with one of the body sensor relaxation techniques. This study aims to analyze whether the increase in positive thoughts can be done with relaxation therapy using body sensors. The method that will be used is a qualitative method with data collection through observation and interviews with 3 subjects. Subjects are teenagers who lack positive thinking. The results obtained are the subject feels fresher body and shows a smile. But the effectiveness of therapy depends on the condition of each subject and requires further therapy to get a clear effect.